Life Experiences of Covid-19 Survivors in Osing Tribe with Zero Deaths Cases - Ikhlas Bekti Dermawan; Sarwono Dwi Saputra; Graceila Oktamanicka Dayu; Novita Surya Putri (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: The Osing Tribe community is still protected from Zero deaths cases due to COVID-19. Objective: The purpose of this study was to explore the life experiences of COVID-19 survivors with zero deaths cases in Osing Tribe. Method: A qualitative with a phenomenological approach was used as the design of this study. The study involved eight Covid-19 survivors in the Osing Tribe who were selected using a purposive sampling technique. Data collection used in-depht interview. Data analysis used the Colaizzi method with the help of Nvivo 12 software. Results: Three themes were analyzed in this study namely 1) coping strategies in the early stages of diagnosis, 2) self-care style, 3) positive support provided by the surrounding environment. Conclusion: Providing support is a custom of the Osing Tribe which aims to maintain the balance of nature and social order. Recommendation: The life experiences of Covid-19 survivors in the Osing tribe indirectly used a bio psychosocial-spiritual approach so that holistic health is realized, positive thinking is based on traditions passed down from generation to generation